PENERAPAN LINGKUNGAN ALAM SEKITAR PADA MATERI KEANEKARAGAMAN HAYATI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SD NEGRI 18 BANDA ACEH - sumiati, Desi Renika; Fita Nelyza; Ruslaini, Ruslaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of utilizing the surrounding natural environment in biodiversity learning materials on the learning outcomes of fifth-grade students at SDN 18 Banda Aceh. The study employed a quantitative approach using a One-Group Pretest–Posttest Design and involved 32 students as participants. The results showed that the mean pretest score of 52.12 increased to 85.62 on the posttest, with an N-Gain score of 0.70, indicating a high improvement category. The hypothesis testing results revealed a significance value of 0.000 < 0.05, indicating that the utilization of the surrounding natural environment had a significant effect on students' learning outcomes. In addition, students' responses to the learning process were classified as very positive, with a percentage score of 85.65%. Therefore, the use of the surrounding natural environment is effective in improving students' learning outcomes in biodiversity learning materials.